Limit analysis and soil plasticity - Chen, Wai-Fah, 1936- (Developments in geotechnical engineering, 1975)
Devoted to the theory and applications of limit analysis as applied to soil mechanics, this text also contains information on soil plasticity and rock-like material such as concrete.